Feasibility and staff acceptability of implementing Xpert HIV-1 viral load point-of-care testing: a pilot study in San Francisco - Kelvin Moore Jr.; Noelle Le Tourneau; Jasmin Alvarez; Santos Rodriguez; Janessa Broussard; Pierre-Cédric Crouch; Jorge Roman; Patricia Defechereux; Jason Bena; Kimberly A. Koester; Lissa Moran; Christopher Pilcher; et al. (BMC Infectious Diseases)
Abstract Background Point-of-care HIV viral load testing may enhance patient care and improve HIV health services. We aimed to evaluate the feasibility and acceptability of implementing such testing in a high-volume community sexual health clinic in the United States. Methods We conducted a cross-sectional, mixed-methods study. Remnant venipuncture specimens from clients undergoing HIV and other sexual health screenings were analyzed using the Xpert® HIV-1 Viral Load assay. Results were compared to COBAS® AmpliPrep/COBAS® TaqMan® HIV-1 Test. Clinical staff observations, study meeting notes, and two semi-structured in-depth interviews with clinical staff were used to understand perspectives on incorporating this testing into clinical practice. Results We analyzed 113 samples from 111 clients. The Xpert assay showed excellent agreement with COBAS, with no clinically significant difference in viral load measurements. Clinical staff found Xpert testing acceptable, based on its ability to provide rapid, accurate test results and potential for bridging patient care gaps. Respondents noted that this testing would be particularly beneficial for individuals in whom barriers to care engagement may complicate follow-up. Challenges in implementation included machine errors as well as concerns related to staff workload, testing logistics, and the need for comprehensive equipment training. Conclusions This study represents the first effort in the United States to describe the feasibility of HIV viral load point-of-care testing in routine care. While the Xpert demonstrated comparable results to standard-of-care testing and staff found it acceptable, further work is needed to develop the workflow and implementation strategies that would enable real-time use and improved patient care. Clinical trial Not applicable.